2022
DOI: 10.3390/cells11121899
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Keratin, Keratin-Associated Proteins and Transglutaminase 1 Are Present in the Ortho- and Parakeratinized Epithelium of the Avian Tongue

Abstract: The lingual mucosa in birds is covered with two specific types of multilayered epithelia, i.e., the para- and orthokeratinized epithelium, that differ structurally and functionally. Comprehensive information on proteins synthesized in keratinocyte during their cytodifferentiation in subsequent layers of multilayered epithelia in birds concerns only the epidermis and are missing the epithelia of the lingual mucosa. The aim of the present study was to perform an immunohistochemical (IHC) and molecular analysis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…Likewise, transglutamination appears to protect the epithelium on the surface of the tongue and in lingual papillae. Recently, immunolabeling studies using cross-reactive antibodies have suggested expression of TGMs in suprabasal epithelial cells of avian tongue [19]. The localization of TGM enzymatic activity in our study is congruent with the pattern of immunoreactivity [19].…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, transglutamination appears to protect the epithelium on the surface of the tongue and in lingual papillae. Recently, immunolabeling studies using cross-reactive antibodies have suggested expression of TGMs in suprabasal epithelial cells of avian tongue [19]. The localization of TGM enzymatic activity in our study is congruent with the pattern of immunoreactivity [19].…”
Section: Discussionsupporting
confidence: 87%
“…Cytokeratins and other proteins of the cornification process are synthesized in the intermediate layer of the cornified epithelia of the avian tongue. Skieresz-Szewczyk et al [ 40 , 41 , 42 ] indicate the presence of avian-specific alpha- and beta-keratin, as well as KAPs (filaggrin and loricrin) and TGM-1 in the intermediate layer of both types of cornified lingual epithelia. The presence of kinase C is required to initiate the synthesis of the above proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical and molecular studies of the cornification process of ortho- and parakeratinized epithelia by Skieresz-Szewczyk et al [ 40 , 41 , 42 ] determined that there is a characteristic pattern of bird-specific alpha- and beta-keratins in the epithelia. Alpha-keratin is mainly accumulated in the lower layers of these epithelia, i.e., in the basal and intermediate layers, and its percentage is, on average, 38–45% [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations